Library Resources: College Students’ Preferences of Cordillera Career Development College, La Trinidad, Benguet - Balao-as, Wilma (Journal of Interdisciplinary Perspectives, 2025)
Despite the availability of library resources and encouragement for students to utilize them, observations indicate a significant underutilization of these materials. It highlights the need to understand the factors influencing students' engagement with library resources. To address this gap, the study examines the extent of students' use of library resources, preferred information sources, and difficulties in using them. The study used a descriptive survey research method, involving 322 Cordillera Career Development College students selected through purposive sampling. The primary data source was a validated survey questionnaire. Results of the study show that, in general, students rarely use the library resources; however, general collection books ranked first as the most frequently utilized. Respondents prefer print resources over non-print resources as information sources. Printed books rank as the most preferred information sources. There is no significant difference in students' preference between print and non-print resources. However, students encounter slight difficulties in utilizing library resources. The three most common challenges they face are difficulty locating needed information resources, insufficient materials available for specific topics, and struggles selecting research topics, making finding relevant resources more challenging. With the results, it can be concluded that while students rely on print, specifically books, and non-print resources for their academic needs, they encounter slight difficulties using them. Therefore, it is recommended that the library improve access to print and digital resources, expand and update its book collection, and strengthen information literacy programs to help students navigate and utilize these resources more effectively.